"Because I'm a girl": Troubling shared visions for music education. (October 2020) - Treacy, Danielle Shannon
In light of recent discussions on the importance of shared visions in teacher education, this inquiry raises necessary questions as to whose visions shape unified and shared visions, and whose remain absent, unspoken, or silenced in the margins. The starting point for this inquiry was a set of visions for music education in Nepal that were co-constructed with over 50 musician-teachers working in the Kathmandu Valley, during a series of 16 workshops guided by Appreciative Inquiry's 4D cycle. Despite the challenges female musician-teachers encounter in their pursuit of music in Nepal, no reference to these injustices was apparent in the resulting shared visions. This inquiry therefore engages with the nature and possible causes of this lack of reference, leaning on economist and philosopher Amartya Sen's (2009) idea of justice and social-cultural anthropologist Arjun Appadurai's (2004) notions of the capacity to aspire and the capacity for voice . The critical (Kuntz, 2015) and reflexive (Alvesson & Sköldberg, 2009) work guiding this inquiry suggests that while the workshops were guided by the aim to be inclusive, the need to come to consensus when co-constructing shared visions both reflected and obscured the injustices experienced by female musician-teachers. The article concludes by offering insights for music teacher education.